Simulation of PEMFC stack for portable power generator application - Siti Najibah Abd Rahman,; Mohd Shahbudin Masdar,; Masli Irwan Rosli,; Edy Herianto Majlan,; Syahril Anuar Md Rejab,; Chew, Chien Lye (Penerbit Universiti Kebangsaan Malaysia, 2018)
Generally, it is possible to reduce the size, cost, and parasitic loss of polymer electrolyte membrane fuel cell (PEMFC) system with an air-cooled system, open cathode and self-humidifying stack for portable fuel cell application. In order to ensure the that PEMFC stack applicable for portable fuel cell application, a mathematical model is useful tool for saving design cost, giving a better system design and operation. Therefore, this study is focused on developing a simplified zero-dimensional mathematical model for self-humidifying and open cathode 200W PEMFC stack for portable fuel cell generator application. The mathematical equations are modelled by using Matlab-Simulink tools in order to simulate the operation of the developed mode. This simulation is then compared to a commercially 200W Horizon PEMFC stack (H-200) for data validation purposes. The air inlet flow rate is chosen to test the sensitivity of the fuel cell stack model. The air inlet stoichiometry of 2, 5, 20, and 50 was varied to generate a different air inlet flow rate. Based on the simulation, air inlet stoichiometry above 15 is sufficient to produce a high output stack voltage. However, in a real operation of the H-200 fuel cell stack system needs air inlet stoichiometry at about 20 because a fan is used to supply air and also the cooling system. High anode and cathode relative humidity result in a high output stack voltage. However, it is better to increase the anode relative humidity than cathode relative humidity to get high output stack voltage.